Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10:
ISBN 13:

Chapter 3 - Adding and Subtracting Fractions - 3.5 Order Relation and the Order of Operations - 3.5 Exercises - Page 245: 67

Answer

$\frac{1}{32}$

Work Step by Step

$(\frac{3}{4})^{2}(\frac{2}{3} - \frac{5}{9}) - \frac{1}{4}(\frac{1}{8})$ = $(\frac{3}{4})^{2}(\frac{6}{9} - \frac{5}{9}) - \frac{1}{4}(\frac{1}{8})$ = $(\frac{3}{4})^{2}(\frac{1}{9}) - \frac{1}{4}(\frac{1}{8})$ = $(\frac{9}{16})(\frac{1}{9}) - \frac{1}{4}(\frac{1}{8})$ = $(\frac{1}{16})(\frac{1}{1}) - \frac{1}{4}(\frac{1}{8})$ = $\frac{1}{16} - \frac{1}{32}$ = $\frac{2}{32} - \frac{1}{32}$ = $\frac{1}{32}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.